Childcare for farm families: A key strategy to keep children safe yet largely absent from farm programming - Becot, Florence; Inwood, Shoshanah; Rissing, Andrea (Frontiers in Public Health, 2022)
Despite long-standing safety recommendations that non-working children be supervised off the worksite by an adult, little is known about farm families' ability to comply. We conducted a review of 92 documents and 36 key informant interviews in three U.S. states (Ohio, Vermont, and Wisconsin) to assess how farm service providers and farm organizations address the intersection of children and childcare with farm work and farm safety in programming. Through their programming, these two groups deeply influence farm families' social systems, affecting farm safety and farm business decisions. Study design and result interpretations were grounded in the women in agriculture literature, which examines the needs and realities of farm women (often the primary caregivers). Most documents reviewed did not address children, and even fewer addressed childcare. Interviews confirm findings of the document review. Despite awareness that farm families juggle work and children, few interviewees explicitly integrated children and childcare topics due to a messy and complex set of individual- and structural-level factors. We identified four possible, overlapping explanations for this tension: valuation of care vs. farm work; farm programming's traditional emphasis on the farm business; alignment of the programming with the agrarian ideal of the family farm; and the mismatch between farm programming scope, resources available, and childcare challenges. We conclude with two main implications for farm safety programs and farm children safety. First, farm programming's reinforcement of the social and cultural expectations regarding children's involvement in the farm operation from a young age could be counterproductive from a farm safety standpoint and miss an opportunity to provide alternative models of childrearing. Second, the invisibility of the lived realities of raising children may lead farm parents to distrust farm programming and deter them from participating.